MODERN DIAGNOSTIC AND TREATMENT PRINCIPLES OF LISFRANC MIDFOOT DISLOCATIONS IN ATHLETES - Răzvan BANDAC (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2012)
Lisfranc midfoot dislocations include bone and ligament injuries to the tarsometatarsal joint complex. Rarelesion, with an incidence rate of 1 to 55,000 patients annually, 20% of injuries remain undiagnosed. Mechanisms ofinjury are direct and indirect, including traffic accidents and sports. Clinical signs and symptoms are: midfoot pain,inability to bear weight, leg deformity and swelling, and plantar ecchymosis. Pedal artery or deep peroneal nerve maybe compromised and the compartment syndrome may occur. Radiographic incidences reveal changes and dislocationsin tarsometatarsal interlining. Stress radiographs are helpful in unstable lesions. CT is used for diagnosis andpreoperative planning. Lisfranc injury classifications can not determine the treatment or suggest prognosis.Nonsurgicaltreatment for stable injuries (<2 mm dislocation) implies immobilization for 4-6 weeks with a non-weight-bearing castOpen reduction with rigid internal fixation is indicated in cases of obvious instability (> 2 mm displacement). Medialand middle columns are fixed with 3.5 mm screws, and lateral column with Kirschner pins. Postoperative care includesearly mobilization, progressive weight-bearing, and osteosynthesis material removal. Primary tarsometatarsalarthrodesis is an alternative in lesions with severe joint damage. Immediate complications are common, includingneurovascular injury and compartment syndrome, and late complications are posttraumatic midfoot arthrosis,algoneurodistrofic syndrome, chronic foot pain, implant deterioration. Patients require a long rehabilitation period. Theincidence of posttraumatic arthritis is high, due to damaged articular surfaces, comminuted fractures, or due to sidemovements, results of unstable osteosynthesis.